Is glycosuria a reliable indicator of adequacy of glucose infusion rate in preterm infants? - Falcão, Mário Cícero; Leone, Cléa Rodrigues; Ramos, José Lauro Araújo (São Paulo Medical Journal, 1999)
CONTEXT: Adequacy of glucose infusion may be monitored via the glycosuria levels, as there is a relationship between glycemia and glycosuria regulated by the renal glucose threshold. In the neonatal period, however, this relationship is not so clear. OBJECTIVE: To evaluate the occurrence of glycosuria in preterm infants submitted to glucose infusion and to verify the relationship between glycosuria and blood glucose level. DESIGN: Accuracy study. SETTING: Neonatal intensive care unit of General Maternity Hospital. PATIENTS: 40 preterm newborns receiving glucose infusion. PROCEDURES: 511 concomitant determinations of glycemia and glycosuria were performed. These 511 pairs were divided into stable and unstable, according to the clinical status of the newborn at the time of data collection, and they were studied in relation to the gestational age, birth weight and glucose infusion rate. RESULTS: The results revealed a greater frequency of glycosuria in gestational age ≤ 30 weeks, birth weight <1500 g and glucose infusion rate > 6 mg/kg/min. Eight (25.8%) episodes of positive glycosuria occurred in the absence of hyperglycemia, indicating only a moderate concordance between them. CONCLUSION: Glycosuria alone is an unreliable marker of blood glucose concentration and adequacy of glucose infusion rate. It is therefore necessary to monitor blood glucose levels in infants submitted to continuous glucose infusion.